KNOWLEDGE AND ATTITUDE OF DENTAL PROFESSIONAL PROGRAM STUDENTS IN PREVENTION OF NOSOCOMIAL INFECTIONS AT GUSTI HASAN AMAN DENTAL HOSPITAL - Aurelia Marsha Denta Oktavia; R. Harry Dharmawan Setyawardhana; Riky Hamdani; Fajar Kusuma Dwi Kurniawan; Rosihan Adhani (FKG ULM, 2024)
Background: Nosocomial infection is one of the reasons for the high morbidity rate in hospitals. Dental professional program students have a risk of contracting or transmitting infection to patients through blood, saliva, lesions, direct contact, or indirect contact when providing care. Dental professional program students need to apply standard precautions to reduce the risk of infection transmission. Purpose: This study aims to analyze the relationship between knowledge and attitude among dental professional program students in prevention of nosocomial infections at Gusti Hasan Aman Dental Hospital. Methods: This type of research is analytical observational with a cross-sectional study design. A sample of 77 dental professional program students was selected using a simple random sampling technique. Collecting data using a questionnaire concerning knowledge, attitude, and behavior in prevention of nosocomial infections. Statistical analysis using the Spearman test. Results: The results showed that as many as 44 people (57.14%) had good knowledge, 53 people (68.83%) had good attitude, and 71 people (92.21%) had good behavior prevention of nosocomial infection. The statistical test results showed that there was a significant relationship between knowledge and behavior to prevent nosocomial infections with a value of p = 0.001 and there was a significant relationship between attitude and behavior prevention of nosocomial infections with a value of p = 0.001. Conclusion: Research shows the need to improve materials and monitor dental professional program students' applied of standard precautions. Good knowledge and a good attitude will be followed by good behavior in the prevention of nosocomial infections.